A Review of Oxygen Use During Chest Compressions in Newborns—A Meta-Analysis of Animal Data - Garcia-Hidalgo, Catalina; Cheung, Po-Yin; Solevåg, Anne Lee; Vento, Maximo; O'Reilly, Megan; Saugstad, Ola; Schmölzer, Georg M. (Frontiers in Pediatrics, 2018)
Background: International consensus statements for resuscitation of newborn infants recommend provision of 100% oxygen once chest compressions are required. However, 100% oxygen exacerbates reperfusion injury and reduces cerebral perfusion in newborn babies. Objective: We aimed to establish whether resuscitation with air during chest compression is feasible and safe in newborn infants compared with 100% oxygen. Methods: Systematic search of PubMed, Google Scholar and CINAHL for articles examining variable oxygen concentrations during chest compressions in term newborns. Results: Overall, no human studies but eight animal studies (n=323 animals) comparing various oxygen concentrations during chest compression were identified. The pooled analysis showed no difference in mortality rates for animals resuscitated with air versus 100% oxygen (risk ratio 1.04 [0.35, 3.08], I2=0%, p=0.94). ROSC was also similar between groups with a mean difference of -3.8 [-29.7 – 22] sec, I2=0%, p=0.77. No difference in oxygen damage or adverse events were identified between groups. Conclusions: Air had similar time to ROSC and mortality as 100% oxygen during neonatal chest compression. A large randomized controlled clinical trial comparing air vs. 100% oxygen during neonatal chest compression is warranted.